Skin paddle and donor site morbidity of myocutaneous latissimus dorsi free flap for reconstruction of large defect - Baharuddin, Shariza (2015)
Myocutaneous Latissimus Dorsi (MCLD) Free Flap has been widely used for reconstructive purpose as it reliable, fairly easy to perform and is believed to have minimal donor site morbidity. We aim to study the effect of raising large skin paddle of MCLD free flap by analyzing the complication of donor and recipient site. Other factors that might affect the complication were also studied. A retrospective study of all consecutive patients operated between 2000 until 2012 that required MCLD free flap was performed. Demographic data, operative details and complications were examined. The QuickDASH questionnaire was performed in patient who was still under follow up and by doing telephone interview to assess the upper limb function. A total of 86 cases were studied (27 women and 59 men) with average age of 32 years old (5 years to 69 years). The most common aetiology for reconstruction was malignancy (48.8%) and trauma (38.4%). The MCLD free flap was mostly used for reconstruction of lower extremity. The mean skin paddle width was 8.01 cm (4cm to 14 cm) and the mean skin paddle size was 206.1cm2 (45cm2 to 440 cm2). Donor complications occurred in 18% cases which include wound breakdown, seroma and blisters formation. There was no significant factor that was found to have association with the development of donor complication. Recipient complication occurs in 48% of cases. Factors that have significant association with development of recipient complication were flap re-exploration (p=0.01), presence of vascular injury (p= 0.01) and long operative time (p=0.02). A total of 22 patients answered the QuickDash questionnaire. There were no significant different between size of skin paddle with limitation of shoulder function. In conclusion, reconstruction of large defect with Myocutaneous Latissimus Dorsi Free flap, the size and width of skin paddle has no significant association with donor or recipient complications. However, there were significant association between presence of vascular injury, long operative time and flap re-exploration with development of recipient complication.